Infrared Heating for Rapid and Localized Shape Transformations of Additively Manufactured Polymer Parts - Oh, Seo-Hyeon; Goo, Bona; Park, Keun (Frontiers in Materials, 2022)
Four-dimensional (4D) printing is an advanced application of additive manufacturing (AM), which enables additional shape transformations over time in response to external stimuli. For appropriate shape transformation, dedicated materials such as shape memory polymers or 3D printers supporting multi-material printing have been used. Recently, a facile 4D printing method was developed which used a fused filament fabrication (FFF) type 3D printer and a plain thermoplastic filament. This method used the anisotropic thermal deformation of the FFF-printed part to intentionally impose anisotropy by programming orthogonal printing paths, which resulted in thermoresponsive shape transformation upon a thermal stimulation. While the previous studies used convective heating as the thermal stimulus and thus required a long heating time of more than 10 minutes, this study uses an infrared (IR) heating to enable rapid thermoresponsive shape transformation. An IR heating system was developed which included an optical focusing unit, a masking unit and a movable heating stage. To investigate the speed of shape transformation, IR heating was performed on a rectangular strip (60 × 6 × 1.6 mm) and the relevant shape transformation time was compared with the previous convective heating result. The shape transformation proceeded rapidly, and after 70 s formed a fully-closed circular shape, corresponding to the 1/10 reduction compared with the convection type heating (more than 13 min). The IR heating was further applied to 2D-to-3D shape transformations of 2D star-shape and flower-shape specimens. For each specimen, a profiled mask was used to selectively irradiate IR on predefined regions and thus to localize the relevant thermoresponsive shape transformation. The global and local IR irradiations were then compared in terms of heating capability and the variability in shape transformations.